METAPHOR AS THE PROJECTION OF PERSONAL LIFE’S WAY - Тищенко, Лілія Валеріївна; Куберська, Дар’я Павлівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article is devoted to the analysis of metaphor phenomenon as a projection display of the individual life. The peculiarities of the relationship between the categories of «life’s meaning», «satisfaction with life», «locus of control», «metaphor of life» in the structure of psychology way of the individual life were examined. The general description of contemporary theoretical concepts of the life path is presented. Linguistic and psychological aspects of metaphor were analyzed. The article argues that the scientific analysis of metaphors is a connection zone of psychological science and practice because it allows you to use application data in a scientific context and giving them a scientific basis. The possibilities of working with the author’s metaphor for interpreting the features of meaningfulness of life, satisfaction with life, styles of organization of life are shown. The results of empirical research of verbal, narrative-metaphorical and personality-stylistic aspects of a personal life path are presented. The possibilities of metaphor as a psychological diagnostic tool for organizing individual way of human’s life in the analysis of the cognitive, emotional, and motivational components of the target activities are shown. It was confirmed that the transformation of the basic metaphor of life is an effective mechanism for organization of the personal style of life.